Groundwater level as an input to monthly predicting of water level using various machine learning algorithms - Sapitang M.; Ridwan W.M.; Ahmed A.N.; Fai C.M.; El-Shafie A. (Springer Science and Business Media Deutschland GmbH, 2023)
algorithm; ground penetrating radar; groundwater; machine learning; resource management; water level; water resource